Sound Absorption Performance Of Natural Kenaf Fibres - Lim, Z.Y.; Putra, Azma; Mohd Nor, Mohd Jailani; Yaakob, Mohd Yuhazri (Elsevier Ltd., 2017)
In recent years, kenaf fibre has been highlighted for its superiority as the filler for composite materials. However, study of the fibres as an acoustic absorber is still lacking. In this paper, the sound absorption of kenaf fibre specimens are studied both under normal and random sound incidence. The normal-incidence sound absorption coefficient measurement was conducted using the impedance tube method. The effects of thickness involving full fibre and air-fibre specimen and the effect of bulk density were discussed. For the random-incidence sound absorption coefficient, the test was conducted in a reverberation chamber. From both methods, the results in general reveal that for bulk density of 140–150 kg/m3 and thickness of 25–30 mm, the absorption coefficient is above 0.5 starting from 500 Hz and can reach 0.85 on average above 1.5 kHz. These frequency bandwidth of absorption and the level of absorption coefficient improve significantly when bulk density and thickness are increased. Additional air gap also improve the absorption toward lower frequency.